Bulk heterojunction perovskite solar cells incorporated with p-type low optical gap conjugated polymers. (March 2022) - Shen, Lening; Zhu, Tao; Zhang, Xinwen; Gong, Keven; Wang, He; Gong, Xiong
Abstract: Perovskite solar cells (PSCs) as alternative cost-effective solar technology have drawn great concentrations in both academic and industrial sectors in the past years. Through the film morphological manipulation of perovskite photoactive layers and generic interfacial engineering, efficient PSCs have been reported. However, intrinsic unbalanced charge transport within the perovskite photoactive layer, which restricted further boost device performance of PSCs, was not fully addressed. In this study, we report high-performance bulk heterojunction (BHJ) PSCs based on the composites composed of n-type Cs0.15 FA0.85 PbI3 (where FA is formamidinium, HC(NH2 )2 ) incorporated with p-type low optical gap conjugated polymer. Compared to pristine Cs0.15 FA0.85 PbI3 thin film, the BHJ composite thin film possesses enhanced and balanced charge carrier mobilities, enlarged crystal sizes, and suppressed non-radiation charge carrier recombination. Most importantly, a photo-induced charge transfer occurs within the BHJ composite thin film. As a result, the BHJ PSCs exhibit a power conversion efficiency (PCE) of 21.08%. In addition, un-encapsulated BHJ PSCs possess remarkably enhanced stability (as they retain 80% of their initial PCE after ~ 200 days in ambient conditions) and diminished photocurrent hysteresis (photocurrent hysteresis index of 0.012) compared to those based on pristine Cs0.15 FA0.85 PbI3 thin film. All these results demonstrate that the PSCs with a BHJ device structure are one of the facile ways to approach high-performance PSCs. Graphical Abstract: Bulk heterojunction perovskite solar cells based on n-type Cs0.15 FA0.85 PbI3 (where FA is formamidinium) incorporated with p-type low optical gap conjugated polymer exhibited 21.8% of power conversion efficiency (PCE), and in addition, un-encapsulated cells retained 80% of their initial PCE after ~ 200 days in ambient conditions and diminished photocurrent hysteresis (photocurrent hysteresis index of 0.012). ga1 Highlights: n-type perovskites mixed with p-type low optical gap conjugated polymers forming bulk heterojunction (BHJ) composites. Enhanced and balanced charge carrier mobilities, enlarged crystal sizes, and suppressed non-radiative charge carrier recombination observed from BHJ composite. Photo-induced charge transfer occurs within BHJ composites. BHJ perovskite solar cells (PSCs) exhibit a power conversion efficiency (PCE) of 21.08%. Un-encapsulated BHJ PSCs possess remarkably enhanced stability and dramatically suppressed photocurrent hysteresis compared to PSCs based on pristine perovskite thin film.